KETERLIBATAN WANITA PADA PERKEMBANGAN KINERJA PERUSAHAAN DENGAN KEKUATAN KELUARGA SEBAGAI VARIABEL MODERATING DI INDONESIA - Ivone Ivone; Dewi, Dewi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Firm performance is one of the measurement to measure how effective the management in a company. This study wants to examine whether female involvement and family power can effect firm performance. The purpose of the study is to analyze whether family power can moderate female involvement to firm performance. The sample of this study is all of the family business which listed in the Bursa Efek Indonesia from 2016 until 2020. Total data being used which fits the requirements are 940 data which includes 188 companies each year. This study uses linear regression analysis and for the program being used to test the variables are Statistical Package for Social Sciences (SPSS) dan E-views. The result shows that family power doesn’t moderate female involvement to firm performance.